Influence of time of annealing on anneal hardening effect of a cast CuZn alloy - Nestorović Svetlana; Ivanić Lj.; Marković Desimir (Journal of Mining and Metallurgy. Section B: Metallurgy)
Investigated cast copper alloy containing 8at%Zn of a solute. For comparison parallel specimens made from cast pure copper. Copper and copper alloy were subjected to cold rolling with different a final reduction of 30,50 and 70%. The cold rolled copper and copper alloy samples were isochronally and isothermally annealed up to recrystallization temperature. After that the values of hardness, strength and electrical conductivity were measured and X-ray analysis was performed. These investigations show that anneal hardening effect at alloys was attained under recrystallization temperature in the temperature range of 180-3000C, followed with an increase in hardness. The amount of strengthening increase with increasing degree of prior cold work. Also the X-ray analysis show the change of lattice parameter during annealing when anneal hardening effect was attained.